Biological polymorphisms of peptidase and α-GPDH in natural populations of the cocoa pod borer Conopomorpha cramerella snellen - Mohd Saahlan, Rusnah; Muhamad, Rita; Tan, S. G.; Gan, Y. Y.; Ahmad, Halmy (Malaysian Plant Protection Society, 1985)
The cocoa pod borer Conopomorpha cramerella (Snellen) (Lepidoptera: Gracilariidae) formerly known as Acrocercops cramerella is considered a new insect attacking cocoa in Sabah, the species being first recorded there in 1980 (M umford, 1984). Although this pest has not been found on cocoa in Peninsular Malaysia, a morphologically similar biotype- of C. cramerella is present in rambutans. With this, it is suspected that there may be two different forms or races of C. cramerella, otherwise two distinct species. The former seems more plausible, with one form attacking rambutans and related fruits and the other form, which could possibly have evolved from the first race in Indonesia, now attacking both cocoa and rambutans in Sabah, Philippines and Indonesia. One of the ways to clarify whether C. cramerella is a sibling species complex (i.e. a group of morphologically similar but reproductively isolated species) is to use the biochemical approach. Electrophoretic techniques permit a precise and relatively simple examination of genetic differences among individual insects and among populations of insects. Electrophoresis had been successfully used to detect the presence of sibling species complexes in several insect species such as the Drosophila willistoni group (Ayala et al.. 1972), the Simulium jenningsi group of black flies (May et al.. 1977), the Myzus persicae group of green peach aphids (May and Holbrook, 1978), the Anopheles gambiae group of mosquitoes (Miles, 1978) and the Perthida glyphopa group of leaf miners (Mahon et al ..1982). No previous work on biochemical polymorphisms using electrophoretic techniques had been done on the cocoa pod borer moth in this country despite it being a major agricultural pest. We now report our screening of the cocoa pod borer for the following biochemical markers: peptidase (PEP), α-glycerophosphate dehydrogenase (α - GPDH), aldehyde oxidase (ALDOX), phosphoglucose isomerase (PGI), isocitrate dehydrogenase (IDH), glutamate oxaloacetate transaminase (GOT) and xanthine dehydrogenase (XDH).